The water-energy nexus in hotels and recreational activities of a mass tourism resort: the case of Benidorm. Issue 4 (16th February 2022) - Yoon, Hyerim; Sauri, David; Rico, Antonio
ABSTRACT: This paper analyses the water-energy nexus (WEN) in hotels and recreational activities of Benidorm, a mass tourism resort on the Spanish Mediterranean coast. A survey was administered to a sample of three- and four-star hotels to estimate (1) water and energy consumption; (2) energy consumption for water uses, and (3) trade-offs between water and energy. Quantitative data was complemented with selected interviews with hotel managers and staff. A strong correlation was found between water and non-renewable energy consumption despite the presence of solar panels in hotels. Hotels with large restaurants (>250 seats) had higher water and energy consumption while spa facilities and lawn areas were positively correlated with energy consumption per guest night. Energy used for water increased according to hotel category. We estimate energy used for water oscillating approximately between 104 and 368 kWh/m 3 for hotels and between 21 and 63 kWh/m 3 for a waterpark. The interviewees revealed little familiarity with WEN despite its potential to achieve water and energy savings. Unsustainable trade-offs between energy and water were found in salty groundwater extraction and disposal for several hotels and for the waterpark. On the positive side, the use of biomass boilers proved to be highly efficient.